PROBLEM GURU MADRASAH IBTIDAIYAH DALAM MENERAPKAN PENILAIAN SIKAP PADA KURIKULUM 2013 - Nadiyah, Nadiyah - (DARRIS: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Attitude is the reaction of students in facing an object. Assessing students' attitudes towards certain objects can be done by looking at the responses observed in dealing with the object in question. In the 2013 curriculum, attitude competencies consisted of two, namely spiritual attitudes and social attitudes. Spiritual attitudes are related to the formation of the character of students who believe and fear. Social attitudes are related to the formation of the character of students who are noble, independent, democratic and responsible. The development of values and attitudes or behaviors as a process of developing moral and behavior is carried out in each subject and in every activity that occurs in class, school, and society. The process in practice, the teacher can add a certain attitude or character value which becomes an extension of the scope of attitude assessment. Based on the basic competency characteristics of spiritual attitudes and social attitudes. This competence can be achieved through indirect learning. Learning is not directly related to the development of values and certain attitudes or behaviors. The problem of the teacher in applying the first attitude assessment is that it is less measurable in conducting assessments during the learning process because the teacher is only more focused on assessing knowledge and skills. The second is the lack of understanding of the teacher in translating core competencies and basic competencies in both aspects of the attitude into indicators of achievement of competencies and understanding of techniques from attitude assessment. The aim is to achieve competence in certain attitudes or character values, the teacher can formulate in advance what aspects of spiritual and social values are to be developed in learning activities, and can reinforce and limit the understanding of each aspect to be developed. Keywords: curriculum 2013, attitude assessment, teacher problem